1994
DOI: 10.1139/f94-301
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation of Subpopulations of Sockeye Salmon (Oncorhynchus nerka) Within Lakes of Alaska, British Columbia, and Kamchatka, Russia

Abstract: Genetic differentiation among subpopulations of sockeye salmon (Oncorhynchus nerka) was investigated within nine intensively sampled lake systems located throughout the species' range using allozyme allelic frequency data collected by researchers in Canada, Russia, and the United States. Allelic frequencies at up to nine highly polymorphic loci were used to examine genetic diversity among 163 samples collected from 68 distinct spawning sites and to identify subpopulation structure within lakes. Significant het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
50
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 11 publications
10
50
0
Order By: Relevance
“…Earlier, analysis of allozyme variation in sockeye salmon showed that geographic distances among populations were only slightly associated with the corresponding genetic distances [7,17,18]. Some authors attribute this mainly to the history of formation of the modern sockeye salmon range, in particular, the origin of geographically close populations from different sources [17,18]. Our data to some extent support this assumption.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Earlier, analysis of allozyme variation in sockeye salmon showed that geographic distances among populations were only slightly associated with the corresponding genetic distances [7,17,18]. Some authors attribute this mainly to the history of formation of the modern sockeye salmon range, in particular, the origin of geographically close populations from different sources [17,18]. Our data to some extent support this assumption.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, this species is expected to display high intraspecific genetic subdivision. Previously, using other molecular markers (allozymes [17,18], combined allozyme and mtDNA data [19], and microsatellite DNA [20][21][22]), it has been shown that genetically different sockeye populations occur at relatively small geographic distances. Possible rapid divergence of sockeye subpopulations, even sympatric ones, has been shown for several Alaskan lakes [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This homing behavior isolates spawning groups so that random genetic drift and local selection produce differences among groups, which can often be detected with molecular markers (Grant et al 1980;Hendry et al 1996Hendry et al , 2000Seeb et al 2000). Although lake and stream spawners often differ genetically, less variation among spawning groups occurs within lakes (Varnavskaya et al 1994;Burger et al 1995;Seeb et al 2000;Habicht et al 2007;Gomez-Uchida et al 2011).…”
mentioning
confidence: 99%
“…For example, anadromous fish usually show high site fidelity for reproduction (Nielsen et al 1999;Waters et al 2000;King et al 2001), which is referred to as philopatry or homing behaviour. When repeated over several generations, natal site fidelity restricts gene flow and allows progressive genetic differentiation and population structuring among spawning populations, even in the absence of geographic barriers (Leider et al 1984;Varnavskaya et al 1994;Hendry et al 1995).…”
Section: Introductionmentioning
confidence: 99%